2018
DOI: 10.1101/448696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

sRNA-target Prediction Organizing Tool (SPOT) integrates computational and experimental data to facilitate functional characterization of bacterial small RNAs

Abstract: Small RNAs (sRNAs) post-transcriptionally regulate mRNA targets, typically under conditions of environmental stress. Although hundreds of sRNAs have been discovered in diverse bacterial genomes, most sRNAs remain uncharacterized, even in model organisms. Identification of mRNA targets directly regulated by sRNAs is rate-limiting for sRNA functional characterization. To address this, we developed a computational pipeline that we named SPOT for sRNA-targetPredictionOrganizingTool. SPOT incorporates existing comp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…An experimental study based on the ligation of Hfq-associated RNAs (Melamed et al, 2016) confirmed the previously observed interaction between cfa mRNA and RydC sRNA, and in addition revealed the potential interactions of the cfa transcript to ArrS, CpxQ, and GadF sRNAs. To verify that ArrS, CpxQ, and GadF sRNAs alter cfa expression post-transcriptionally in vivo, we constructed two translational cfa’-’lacZ fusions under the control of the arabinose-inducible P BAD promoter (King et al, 2019). One fusion contains the 212-nt 5’ UTR and the first 36 codons of cfa (cfa’-’lacZ-Long, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An experimental study based on the ligation of Hfq-associated RNAs (Melamed et al, 2016) confirmed the previously observed interaction between cfa mRNA and RydC sRNA, and in addition revealed the potential interactions of the cfa transcript to ArrS, CpxQ, and GadF sRNAs. To verify that ArrS, CpxQ, and GadF sRNAs alter cfa expression post-transcriptionally in vivo, we constructed two translational cfa’-’lacZ fusions under the control of the arabinose-inducible P BAD promoter (King et al, 2019). One fusion contains the 212-nt 5’ UTR and the first 36 codons of cfa (cfa’-’lacZ-Long, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…cfa’-’lacZ -Long, cfa’-’lacZ -Short, cfa’-’lacZ -ΔsRNABS, and cfa’-’lacZ- ΔHfqBS were constructed by PCR amplifying the cfa 5’ UTR fragment of interest from DJ624 using a fusion-specific forward primer containing flanking homology to P BAD and the reverse primer O-AK24R, which contains flanking homology to lacZ and anneals in the cfa coding region (Table EV3). cfa’-’lacZ -Long and cfa’-’lacZ -Short were constructed by A.M. King (King et al, 2019). cfa’-’lacZ -Long H1 and H4 were constructed by using a forward primer containing the desired point mutations and flanking homology to P BAD and reverse primer O-AK24R to PCR amplify the cfa 5’ UTR fragment of interest from DJ624 (Table EV3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation